Fournier Gangrene Associated with Sodium-Glucose Cotransporter-2 Inhibitors: A Pharmacovigilance Study with Data from the U.S. FDA Adverse Event Reporting System - Yang Hu; Ziyu Bai; Yan Tang; Rongji Liu; Bin Zhao; Jian Gong; Dan Mei (Journal of Diabetes Research)
Background. The U.S. Food and Drug Administration (FDA) released a safety warning of Fournier gangrene (FG), a rare but serious adverse effect of sodium-glucose cotransporter-2 (SGLT2) inhibitors in August 2018. However, existing studies have focused mainly on individual FG case reports. Although several previous studies conducted reviews of cases, objective scientific analysis was not applied, and the prognosis data were inadequate. Objective. This study is aimed at presenting data supplementary to existing studies by analysing postmarketing adverse event reports in the FDA Adverse Events Reporting System (FAERS) database. Multiple statistical analysis methods were applied to evaluate the potential association between SGLT2 inhibitors and FG, thus providing reliable and professionalized medication usage recommendations for SGLT2 inhibitors in clinical practice. Methods. Disproportionality analysis and Bayesian analysis were applied for data mining among the suspected adverse event reports of FG associated with SGLT2 inhibitors recorded in the FAERS database during the period from January 2004 to September 2019. Results. There were 542 FG cases identified in the FAERS database in patients receiving SGLT2 inhibitors. Among all SGLT2 inhibitor therapies, empagliflozin was associated with the highest number of FG reports (232 in total), while empagliflozin plus metformin had the strongest association with FG occurrence with the reporting odds ratio (ROR 54.79, 95% two-sided CI 31.56 to 95.12) and proportional reporting ratio (PRR 53.36, χ2 666.70). There were 391 patients who underwent initial or prolonged hospitalization (72.14%), and 26 patients died (4.81%). Three new FG cases caused by ertugliflozin were found in 2019. Conclusion. The analysis of SGLT2 inhibitor-associated FG reports in the FAERS database identified signals between the drug and adverse events of interest. It also provides comprehensive information on the characteristics of FG onset and prognosis. Clinicians should pay more attention to this rare but severe adverse event when prescribing SGLT2 inhibitors in clinical practice.